Transforming Education Management Strategies for Realizing Innovation and Creativity Based Schools - Sagaf S.Pettalongi (Journal of Pedagogi, 2025)
Rapid changes in the globalized world require the education system to not only adapt, but also be able to create a learning environment that encourages innovation and creativity. This research discusses the transformation of education management strategies as a strategic approach in building schools based on innovation and creativity. The main objective of this study is to describe how adaptive and transformative managerial strategies can support the creation of an educational ecosystem that is dynamic, responsive and relevant to the challenges of the times. The research approach is qualitative with literature study and case analysis methods that focus on best practices in education management in various innovative institutions. The results show that the success of education management transformation depends on several key factors, including visionary leadership, close collaboration between stakeholders, strategic use of technology, strengthening reflective culture, and supporting the professional development of teachers and school staff. In addition, flexibility in the curriculum and project-based learning approaches are also an important part of supporting learners' creativity. This research provides theoretical and practical contributions in the field of education management, as well as offering strategic recommendations for policy makers and education actors in designing and implementing strategies that can realize schools as centers of innovation and creativity